Etiology of first-ever ischaemic stroke in European young adults: the 15 cities young stroke study - Yesilot Barlas, Nilufer; Putaala, J.; Waje‐Andreassen, U.; Vassilopoulou, S.; Nardi, K.; Odier, C.; Hofgart, G.; Engelter, S.; Burow, A.; Mihalka, L.; Kloss, Manja; Ferrari, J.; et al. (European journal of neurology, 2013)
Background and purpose Risk factors for IS in young adults differ between genders and evolve with age, but data on the age- and gender-specific differences by stroke etiology are scare. These features were compared based on individual patient data from 15 European stroke centers. Methods Stroke etiology was reported in detail for 3331 patients aged 15-49 years with first-ever IS according to Trial of Org in Acute Stroke Treatment (TOAST) criteria: large-artery atherosclerosis (LAA), cardioembolism (CE), small-vessel occlusion (SVO), other determined etiology, or undetermined etiology. CE was categorized into low- and high-risk sources. Other determined group was divided into dissection and other non-dissection causes. Comparisons were done using logistic regression, adjusting for age, gender, and center heterogeneity. Results Etiology remained undetermined in 39.6%. Other determined etiology was found in 21.6%, CE in 17.3%, SVO in 12.2%, and LAA in 9.3%. Other determined etiology was more common in females and younger patients, with cervical artery dissection being the single most common etiology (12.8%). CE was more common in younger patients. Within CE, the most frequent high-risk sources were atrial fibrillation/flutter (15.1%) and cardiomyopathy (11.5%). LAA, high-risk sources of CE, and SVO were more common in males. LAA and SVO showed an increasing frequency with age. No significant etiologic distribution differences were found amongst southern, central, or northern Europe. Conclusions The etiology of IS in young adults has clear gender-specific patterns that change with age. A notable portion of these patients remains without an evident stroke mechanism according to TOAST criteria.